Caffeine Consumption, Sleep Quality and Mental Health Outcomes Among Malaysian University Students - Norhaslina Sulaiman; Asma Ali; Muhamad Khairul Zakaria; Mohd Radhi Abu Shahim; Sim Why Jean; Abbe Maleyki Mhd Jalil (Medsci Publications, 2024)
Background: Recognizing the scarcity of data on caffeine consumption among university students in Malaysia, this study was designed to first characterize the habitual caffeine intake within this group. This study further investigated the potential association between these caffeine consumption patterns and sleep quality and mental health status. Methodology: The study employed an online self-administered questionnaire to assess habitual caffeine intake from various products. Sleep quality and mental health were evaluated using the Pittsburgh Sleep Quality Index (PSQI) and the Depression, Anxiety, and Stress Scale-21 (DASS-21), respectively. Results: 78% of the respondents consumed caffeinated products daily within the safe level recommended by the European Food Safety Authority (£400mg/day). Only 2.6% of the students consumed caffeine exceeding the recommended limit. The median total daily caffeine intake was 100mg/day. Most students had poor sleep quality (77.3%), with 43.5%, 49.5%, and 33.0% reporting varying levels of depression, anxiety, and stress, respectively. Odds ratio calculations revealed respondents consuming less than or more than 400 mg/day of caffeine did not show significantly different odds of poor sleep quality, depression, anxiety, or stress compared to non-consumers. Conclusions: This study highlights the need for further localized research on caffeine's effects among Malaysian university students regarding caffeine consumption, sleep, and mental health.